Accounting research and the significance test crisis. (December 2022) - Johnstone, David
Abstract: The emerging or at least threatening "significance test crisis" in accounting has been prompted by a chorus across multiple physical and social sciences of dissatisfaction with conventional frequentist statistical research methods and behaviors, particularly the use and abuse of p -levels. There are now hundreds of published papers and statements, echoing what has been said behind closed doors for decades, namely that much if not most empirical research is unreliable, simply wrong or at worst fabricated. The problems are a mixture of flawed statistical logic (as Bayesians have claimed for decades), " p -hacking" by way of fishing for significant results and publications, selective reporting or "the file drawer problem", and ultimately the "agency problem" that researchers charged by funding bodies (their Universities, governments and taxpayers) with conducting disinterested "objective science" are motivated more by the personal need to publish and please other researchers. Expanding on that theme, the supply of empirical research in the "market for statistical significance" is described in terms of "market failure" and "the market for lemons".